Evaluation Properties and PNA Analysis for Different Types of Lubricants Oils - Salim Bded, Asaad; Hameed khlaif, Tahseen (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
A study of characteristics of the lubricant oils and the physical properties is essential to know the quality of lubricant oils. The parameters that lead to classify oils have been studied in this research. Three types of multi-grades lubricant oils were applied under changing temperatures from 25 oC to 78oC to estimate the physical properties and mixture compositions. Kinematic viscosity, viscosity gravity constant and paraffin (P), naphthenes (N) and aromatics (A) (PNA) analysis are used to predict the composition of lubricants oil. Kinematic viscosity gives good behaviors and the oxidation stability for each lubricant oils. PNA analysis predicted fractions of paraffin (XP), naphthenes (XN), and aromatics (XA) for each one give us a good value for sample 3 (15W40) leads to suitable classification for this type multi-grade oils by kinematic viscosity